The Sarawak report the inside story of the 1MDB exposé - Brown, Clare Rewcastle (Gerakbudaya Enterprise, 2018)
The Sarawak Report is the stranger-than-fiction tale of how one womanuncovered the world's biggest theft which, in 2018, brought down theMalaysian government.Investigating the deforestation of Sarawak, Borneo, and the dispossession ofits people, journalist Clare Rewcastle Brown followed a trail of corruptionthat led her to the heart of Malaysian politics and to Prime MinisterNajib Razak himself. Determined that the public should know the truth,she started a blog, which became Malaysia's go-to news outlet for informationthat the government was trying to suppress - and whistleblowers wanted toget out. She was soon running a radio station too